2017
DOI: 10.2147/ndt.s129480
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbid psychiatric disorders on methadone maintenance treatment in opioid use disorder: a prospective cohort study

Abstract: ObjectiveThere is a significant interindividual variability in treatment outcomes in methadone maintenance treatment (MMT) for opioid use disorder (OUD). This prospective cohort study examines the impact of comorbid psychiatric disorders on continued illicit opioid use in patients receiving MMT for OUD.MethodsData were collected from 935 patients receiving MMT in outpatient clinics between June 2011 and June 2015. Using linear regression analysis, we evaluated the impact of having a comorbid psychiatric disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 61 publications
2
55
1
1
Order By: Relevance
“…Clinical Determinants, Harms, and Prognosis of Co-occurring BPD and SUD While population prevalence rates for BPD are estimated to be between 1 and 6% (Trull et al, 2016;Trull, Sher, Minks-Brown, Durbin, & Burr, 2000), rates of BPD among treatment-seeking substance users are estimated to be as high as 65% (Darke, Ross, Williamson, & Teesson, 2005;Rosic et al, 2017;Trull et al, 2000). The exacerbation of symptomatology through the interaction between the disorders is of particular relevance to treatment planning as this contributes to chronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Determinants, Harms, and Prognosis of Co-occurring BPD and SUD While population prevalence rates for BPD are estimated to be between 1 and 6% (Trull et al, 2016;Trull, Sher, Minks-Brown, Durbin, & Burr, 2000), rates of BPD among treatment-seeking substance users are estimated to be as high as 65% (Darke, Ross, Williamson, & Teesson, 2005;Rosic et al, 2017;Trull et al, 2000). The exacerbation of symptomatology through the interaction between the disorders is of particular relevance to treatment planning as this contributes to chronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Participants also underwent a structured clinical interview, administered by trained research staff, and provided urine and blood samples. Please see previous literature for a more thorough description of GENOA methodology [31,32]. The POST study began in 2018 as an extension to GENOA, with similar data collection protocol and inclusion criteria, barring participants now meeting criteria for OUD as diagnosed with the DSM-5 [12].…”
Section: Datamentioning
confidence: 99%
“…[7][8][9][15][16][17][18] Logistic regression models have been developed to predict patients who may be susceptible to prescription opioid abuse. [7][8][9] Comorbid psychiatric disorders have been considered for their impact on the efficacy of various treatments of opioid use disorder, [15] and literature reviews have found high rates of co-occurrence between opioid use disorder and anxiety, psychiatric comorbidity, and drug use. [16][17][18] These studies focus on either city-level spatiotemporal patterns, and/or solely on abuse of a single class of opioids.…”
Section: Introductionmentioning
confidence: 99%